Evaluation of Health Visitor and Family Medicine Units in Babylon's Healthcare Centers - Anied, Ayad abbas (American Journal of Biology and Natural Sciences, 2025)
Background: The Iraqi Ministry of Health (MoH) has developed a standardized package of basic health services for all primary healthcare (PHC) facilities to enhance service quality. This study evaluates service availability and facility needs in the family health units in Babylon. Methods: This cross-sectional study was conducted in three family healthcare sectors (the first Al-Hillah sector, Al-Musayyib sector, and Al-Hashemiyyah sector), which includes 6 out of 23 primary healthcare centers in the Babylon Governorate. The data collection started on March 3, 2022, and ended on August 27, 2022, and was randomly chosen from all sectors. Results: According to this study, the family health unit had a poor mean score of 48.03±17.97. Similarly, the health visitor indicators had an inadequate level of assessment, with a mean score of 46.87±14.09. In conclusion, this revealed a study that the primary health care centers evaluated had poor scores in all the final evaluation indicators for the family health unit and the health visitor unit.